Acute and late toxicity of bilateral orbital irradiation in the management of primary intraocular lymphoma. Issue 11 (1st November 2016) - Milgrom, Sarah A.; Cheah, Chan Y.; Pinnix, Chelsea C.; Smith, Grace L.; Dabaja, Bouthaina S.; Horace, Patricia; Chevez-Barrios, Patricia; Fowler, Nathan H.; Gombos, Dan S.
Abstract: Primary intraocular lymphoma (PIOL) is a rare malignancy with poor outcomes. Concerns regarding toxicity lead some clinicians to exclude orbital radiation therapy (RT). We aimed to quantify the ocular toxicity of RT in 11 PIOL patients treated with chemoimmunotherapy and bilateral orbital RT (median 36 Gy). A multidisciplinary team, including an ocular oncologist, followed patients for a median of 42 months after RT. Common adverse events included dermatitis (100%), conjunctivitis (82%), xerophthalmia (64%), and keratopathy (45%). All phakic eyes developed cataracts (100%); correction resulted in good vision recovery. New, visually significant retinopathy was observed in only one eye (<5%) and affected a patient with preexisting diabetes. This report suggests that severe, vision-threatening complications following orbital RT are uncommon. In the absence of comorbidities, orbital RT should not be withheld due to fear of vision-threatening toxicity. The risk of toxicity may be augmented by comorbidities, so an individualized approach is recommended.